Legal regime for Antarctic governance: Challenges and opportunities - S. Lijagegnehu Biru (Юридичний часопис Національної академії внутрішніх справ)
The Antarctic Treaty System, a cornerstone of international cooperation, faces increasing challenges as the 21st century unfolds. This study examined the effectiveness of Antarctic Treaty System in addressing contemporary issues such as marine environmental protection, bioprospecting, and climate change. It analysed the strengths and weaknesses of the treaty, identified gaps in its coverage, and assessed its adaptability to future challenges. This study employed an interdisciplinary approach combining legal analysis, policy analysis, comparative analysis, and critical analysis, and delved into the treaty's provisions, limitations, and potential for reform. The findings of the study showed that although the Antarctic Treaty System plays a vital role in preserving the Antarctic as a global common, its ability to withstand new threats is limited. The study emphasised the need for a comprehensive system of marine protected areas, stricter regulations on bioprospecting, and stronger enforcement mechanisms. Key conclusions included the need for mandatory environmental impact assessments, the expansion of marine protected areas, sustainable tourism management, and effective climate change mitigation strategies. In addition, the article recommended strengthening the inspection regime, promoting international cooperation, recognising the rights of indigenous peoples, and intensifying scientific research. By addressing these issues and implementing the proposed reforms, the Antarctic Treaty System can continue to protect Antarctica’s unique environment and ensure its long-term sustainability